A study on the early streamer emission (ESE) lightning protection system - Ngu, Eng Eng (2004)
Early Streamer Emission (ESE) Lightning Protection (LP) system is a relatively new approach in solving the perennial problem of lightning damage, which has been associated with the use of Franklin Rod (FR). Based on theoretical consideration and some previous work by several researchers, the ESE is believed to be providing more effective protection against lightning than would a FR system. However, the scientific and technical basis to support the belief of this improved system is still not concrete enough and this then inevitably leads to the efficacy of these technologies still remain opened for further study and improvement. The new system is equipped with a special device that is used to extend the effective range of protection over that of the FR. In this work, results have been obtained from the simulated testing carried out in the laboratory and also from field monitoring of real FR and ESE system installed in the university campus. Visits to several sites, which employ these systems, have enabled physical observation of the after effects of lightning be recorded for analyses. The results show that slightly rounded air terminal, which is typical of ESE system offer better interception ability than that of sharp terminals, which is the typical FR design. It is also shown that ionizing the air around the tip of the terminals can enhance its effectiveness. This conclusion is substantiated by field observation obtained from the installed systems where the ESE system has been found to intercept more lightning strikes than that by the FR.